(untitled) (Bangladesh Journal of Plant Taxonomy, 2009)
Ten taxa belonging to Chlorophyceae, Cyanophyceae, Bacillariophyceae and Euglenophyceae, and one with an uncertain taxonomic position have been described in this paper. Of these, 10 taxa have been found to be globally rare and new records for Bangladesh, whereas Strombomonas islamii Khondker sp. nov. has been described as new to science. Keywords: Rare species; Strombomonas islamii Khondker; Ponds; Bangladesh. DOI: 10.3329/bjpt.v16i1.2734 Bangladesh J. Plant Taxon. 16(1): 1-8, 2009 (December)